Initiation of Para-Badminton through the "Shuttle Time" teaching program - Aline Miranda Strapasson; Keiko Verônica Ono Fonseca; Maria Luiza Tanure Alves; Justin A. Haegele; Edison Duarte (Universidade Estadual de Campinas, 2020)
Introduction: Para-Badminton (PBd) is an adapted sport for people with disabilities. One avenue to make badminton popular around the world is a badminton teaching program called "Shuttle Time". This resource helps coaches develop skills, knowledge and confidence to plan and offer safe and fun badminton classes. Objective: The purposes of this report were to apply the "Shuttle Time" teaching program for persons with physical disabilities (PD), to adapt activities proposed by the program, if necessary, and describe suggestions for the adaptations. Conclusion: The final observations in this report refer to the adaptations of the "Shuttle Time" teaching program for persons with PD, by supplementing it with more activities can better serve children with PD, supporting badminton teaching to this population.